Ochrona czci w prawie karnym i w prawie cywilnym: [Protection of honour in penal and civil law] (Studia Prawnicze / The Legal Studies, 1983)
In the binding system of Polish law there are three ways of protecting honour: by civil law, by penal law and - in special cases - by labour law. The work compares two first ways, and, in particular, it tries to establish whether' the injured person is, de lege lata, adequately protected.The observation of functioning of both systems of protection leads to the conclusion that in spite of differences in legislative solutions in penal and civil_ law, premises of protection by ,civil and penal Law undergo a process of assimilation. It takes place mainly under the influence of civil courts decisions in which_ abstract premises of protection by civil law are understood as concrete premises provided for in penal law.A considerable convergence can also be observed in the field of sanctions_ This results from the tact that sanctions characteristic exclusively of one system of protection play in practice - mainly with a view to a small frequency of occurence - a considerably smaller role than sanctions fulfiling similar functions.The article also points to the obstacles existing both in penal and civil law, rendering and sometimes even making impossible to exercise the protection.The considerations allow to draw a conclusion that border line of influence of civil and penal law in the sphere of protection of honour have not been marked out in the best possible way. It seems that the evolution of accepted norms Should tend towards certain liberality of principles of responsibility so that minor infringements of honour be protected only by civil law. Such a modification would make the binding system of protection of honour more clear and increase its effectiveness.